The end of straight supremacy : realizing gay liberation - Gilreath, Shannon, 1977-. (Cambridge : Cambridge University Press, 2012)
'This book presents a cohesive theory of gay life under straight domination and calls for the difficult task of rethinking what liberation and equality really mean'--
Includes bibliographical references and index.
Keywords: Gays -- United States -- Social conditions; Gay rights -- United States -- History; Gay liberation movement -- United States -- History